2007
DOI: 10.1590/s0100-879x2006005000141
|View full text |Cite
|
Sign up to set email alerts
|

Low expression of antigen-presenting and costimulatory molecules by lung cells from tuberculosis patients

Abstract: Costimulatory and antigen-presenting molecules are essential to the initiation of T cell immunity to mycobacteria. The present study analyzed by immunocytochemistry, using monoclonal antibodies and alkaline phosphatase-anti-alkaline phosphatase method, the frequency of costimulatory (CD86, CD40, CD40L, CD28, and CD152) and antigen-presenting (MHC class II and CD1) molecules expression on human lung cells recovered by sputum induction from tuberculosis (TB) patients (N = 22) and non-TB controls (N = 17). TB cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Moreover, there have been only a few conflicting reports on group I CD1 expression on APC in lungs and/or lymph nodes from patients affected by TB (4,8,23). Thus, if group I CD1-restricted T lymphocytes contribute to the effective defense against M. tuberculosis (12), the inhibition of CD1 expression might allow M. tuberculosis to effectively evade T-cell surveillance during infection in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there have been only a few conflicting reports on group I CD1 expression on APC in lungs and/or lymph nodes from patients affected by TB (4,8,23). Thus, if group I CD1-restricted T lymphocytes contribute to the effective defense against M. tuberculosis (12), the inhibition of CD1 expression might allow M. tuberculosis to effectively evade T-cell surveillance during infection in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that TB patients have significantly lower HLA-DR expressing cells, which may negatively affect T-cell immune responses and thus facilitate the disease progression [21]. For this reason Dzherelo appears to have a positive effect on a subset of activated T lymphocytes which may favorably influence the treatment outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, Bhatt et al reported that B7.1 and B7.2 (the murine homologs of CD80 and CD86) knockout mice are more susceptible to M. tuberculosis infection and that the B7 receptor signaling pathway is critical for long-term containment of infection within lung granulomas (Bhatt et al, 2009). In another study, cells recovered from induced sputum from patients with tuberculosis and controls were analyzed, and it was observed that cells from the infected patients had lower expression levels of co-stimulatory molecules (CD80 and CD86) (Flores-Batista et al, 2007). Decreased expression of these molecules, which are involved in antigen presentation and T-cell activation, in patients could lead to decreased T-cell recognition during M. tuberculosis infection.…”
Section: Discussionmentioning
confidence: 99%